The impact of stirrups on the composite action of concrete-filled steel tubular stub columns under axial loading. (April 2021) - Lu, De-ren; Wang, Wen-jun; Ding, Fa-xing; Liu, Xue-mei; Fang, Chang-jing
Abstract: In view of lacking in-depth study on the influence of stirrups on the confinement action of stirrup-confined concrete-filled steel tubular (CFT) stub columns, this paper takes concrete-filled round-end and rectangular weathering steel tubular (FWST) stub columns as research objects, and carries out 8 experimental studies on FWST stub columns under axial loading. The results indicated that the basic mechanical properties of FWST stub columns were similar to those of CFT stub columns. Besides, studies on parametric analysis and composite action among steel tube, stirrups and the core concrete have been carried out using FE modelling which had been verified using the test data. The analysis showed that stirrups not only directly restrained the concrete but enhanced the confinement effect from steel tube on concrete. The greater the aspect ratio B / D was, the greater the ultimate bearing capacity of stirrup-confined round-end and rectangular CFT stub columns increased. In addition, Simplified formulas were proposed to estimate the ultimate bearing capacity of stirrup-confined round-end and rectangular CFT stub columns considering the influence of stirrup ratio on the constraint coefficient under different aspect ratio B / D . Compared with the existing formula using the experimental and numerical results, it found that the formulas of ultimate bearing capacity of stirrup-confined round-end and rectangular CFT stub columns proposed in this paper were accurate and more reasonable.